Automatic adaptation in self-monitoring systems for MCI patients: conceptual approach and a software prototype - Cruz, Davi de Oliveira; Chechetti Junior, Carlos Alberto; Brucki, Sonia Maria Dozzi; Takada, Leonel Tadao; Nunes, Fátima L. S. (Proceedings of the Life Improvement in Quality by Ubiquitous Experiences Workshop (LIQUE), 2022)
With the growth of access to mobile devices, more applications are emerging for the most diverse purposes. In the health area, applications for monitoring patients with some type of dementia facilitate the day-to-day tasks of both patients and caregivers. However, a remaining challenge is to maintain patient loyalty in using the application so that their data can be constantly collected and analyzed, and treatments and follow-ups can be effective. One approach to trying to improve this situation is to customize and adapt the system, bringing it closer to the preferences of each user. This paper presents the conceptual approach and a prototype of a mobile self-monitoring system for patients with Mild Cognitive Impairment (MCI), a pre-dementia condition, which aims to maintain user loyalty in using the system.